Spermogram variables analysis in the infertility consultation patients of the Cienfuegos municipality - Mabel Rodríguez Monteagudo; Raidell Avello Martínez; Amanda Avello Rodríguez; Aida María Reyes Pérez (Medisur)
Background: Semen quality analysis is considered a basic element in the evaluation of male fertility. Objective: to analyze the spermogram values in patients treated at the Cienfuegos Municipal Infertility Clinic. Methods: descriptive study, which included 128 samples resulting from spermograms performed on patients treated at the Cienfuegos municipal infertility clinic, between 2019 and 2020. Spermograms record the variables: age, volume, concentration, mobility, morphology, and vitality. These variables were compared with the reference values proposed by the World Health Organization. Results: regarding the concentration, it highlighted that the values oscillated in a wide range, from 0 to 350 mmol / L-1, with a mean of 89.1; while the mobility of the spermatozoa showed very low values, even some with 0%. Total mobility (fast mobility plus slow mobility) was 57.7%. The percentage of sperm with an adequate morphology was 46.3, while the vitality was 71.8%. Conclusion: Most of the analyzed samples showed normal values in all parameters. The number of patients with leukospermia was significant, a parameter that is probably directly related to infertility in these subjects.